A unique, intuitive, creative, innovative, bold scientist in endless quest of the truth and a giant in high-altitude medicine: Prof. Dr. Gustavo Zubieta-Castillo, "The Parvatha Guru" (May 20, 1926-September 17, 2015) - Gustavo Zubieta-Calleja; Natalia Zubieta-De Urioste (Wolters Kluwer Medknow Publications, 2016)
Professor Gustavo Zubieta-Castillo - The Mountain Guru, Bolivian visionary, loved art and science. He was a word class pioneer and defender of life and medicine at high altitude. In 1964, after his observations of the perfused heart in dogs, he affirmed that the hearts of high-altitude residents are much more resistant to hypoxia than those at sea level. He clarified misconceptions about lung diseases at high altitude, which were improperly termed "loss of adaptation." His original and unique views on what was called chronic mountain sickness (CMS), a term he proposed be discarded and be rather expressed as polyerythrocythemia (as a more precise symptomatic description of multiple pathologies in the hypoxic environment of high altitude). He created the "triple hypoxia syndrome," an essential description to explain the momentary decrease of PaO 2 in polyerythrocythemic patients. His concepts of hypoxia gave rise to the formulation of the high-altitude adaptation formula. On his obituary, legendary respiratory physiologist Prof. John B. West stated, "He was a remarkable man and our discipline has lost a giant." Renowned Environmental scientist Prof. Thuppil Venkatesh, a long-time friend of Prof. Gustavo Sr., stated, "We lost one of the most valuable and precious personalities... a great loss to the world scientific community." Prof. Gustavo's son Prof. Dr. Gustavo Zubieta Calleja is also a renowned pulmonologist like his legendary father and keeping his illustrious father's legacy with pride and honor at his "High Altitude Pulmonary and Pathology Institute," La Paz, Bolivia.